Modeling and evaluating site and provenance variation in height–diameter relationships for Betula alnoides Buch.–Ham. ex D. Don in southern China - Yin, Mingyu; Wang, Chunsheng; Wang, Huan; Han, Qiang; Zhao, Zhigang; Tang, Cheng; Guo, Junjie; Zeng, Jie (Frontiers in Plant Science, 2023)
Height-stem diameter at breast height (H-D) relationship is correlated with timber yield and quality as well as stability of forest, and is crucial in forest management and genetic breeding.It is influenced by not only environmental factors such as site quality and climate factors, but also ; and genetic control is also one key impact factor of H-D relationship, which is mostly neglected. A dataset of tree height and DBH of 25 provenances of Betula alnoides Buch.-Ham. ex D.Don at four sites was used to model the H-D relationship. The dummy variable nonliner mixed-effect equations were used applied to evaluate the effects of sites and provenances on variations of H-D relationship, and applied to select superior provenances of B. alnoides.Weibull equation was selected as the base model for H-D relationship. The sites affected asymptotes of H-D curves, and the provenance effect on asymptotes of H-D curves varied across sites. Taking above-mean average DBH growth and lower asymptote of H-D curves as the indicators, five excellent provenances at each site were screened out at each site with a rate of 20%. Their selection gains of individual volume ranged from 1.99% to 29.81%, and their ose of asymptote parameter (kj) and height-to-DBHH-D ratio decreased were 7.17%-486.05% and 3.07-4.72% lower thancompared to the relevant total means at four sites, respectively.Genetic selection based on the H-D relationship could promote selection efficiency of excellent germplasms and were beneficial for the large-sized timber production of B. alnoides.